Vehicle technical inspection results in relation to EU directives and selected EU countries - Klemenc, Jernej (Strojniški vestnik, 2023)
Although road accidents caused by defective vehicles are relatively rare, the roadworthiness of vehicles is important for road safety. In the European Union, the technical conditions that need to be fulfilled by the vehicles using public roads are regulated by EU directives. According to these directives, technical inspections are organized in every EU country. Our study analyzed the vehicle technical inspections in Slovenia over four consecutive years. The statistics for passenger cars and commercial vehicles are compared with two other EU countries: Germany and Finland. From this comparison, it follows that certain differences exist between the countries, although vehicle technical inspections are regulated by the same EU directives. Finally, multivariate regression models were built to predict probabilities of various vehicle defects detected during regular technical supervision as a function of the vehicle’s age. It was found that the probability of fault detection can be effectively modelled as a function of vehicle age.
Keywords: commercial vehicles; fault statistics; gospodarska vozila; osebna vozila; passenger vehicles; statistical modelling; statistično modeliranje; statistika napak; technical supervision; tehnični pregledi